2016
DOI: 10.1111/ele.12601
|View full text |Cite|
|
Sign up to set email alerts
|

Options of partners improve carbon for phosphorus trade in the arbuscular mycorrhizal mutualism

Abstract: The mutualism between plants and arbuscular mycorrhizal fungi (AMF) is widespread and has persisted for over 400 million years. Although this mutualism depends on fair resource exchange between plants and fungi, inequality exists among partners despite mechanisms that regulate trade. Here, we use (33) P and (14) C isotopes and a split-root system to test for preferential allocation and reciprocal rewards in the plant-AMF symbiosis by presenting a plant with two AMF that differ in cooperativeness. We found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 32 publications
1
55
0
Order By: Relevance
“…For instance, Argüello et al . () found that diversity of AMF promotes cooperation between plants and AMF. However, promoting diversity and inoculum density of AMF may trade‐off their ability to stimulate plant productivity in some instances.…”
Section: Fungal Genotypementioning
confidence: 99%
“…For instance, Argüello et al . () found that diversity of AMF promotes cooperation between plants and AMF. However, promoting diversity and inoculum density of AMF may trade‐off their ability to stimulate plant productivity in some instances.…”
Section: Fungal Genotypementioning
confidence: 99%
“…In general, the extent to which one partner or the other is in control remains unclear, particularly in natural, diverse AMF communities, although recent evidence suggests that it is beneficial for a tree to maintain a diversity of fungal symbionts throughout its lifetime (Arguello et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Because the commercial AMF mix that we used was purported to consist of four AMF species, the different effects of AMF availability on herbivore performance may be a function of differential colonization by AMF species under medium and high AMF availability. AMF species vary in their relative trading of nutrients (Lendenmann et al, 2011;Thonar et al, 2014;Argüello et al, 2016) and effects on plant phenotype (Gehring and Bennett, 2009;Bennett et al, 2013) which can alter herbivore performance (Roger et al, 2013;. However, cloning and sequencing of the AMF mix, and roots from milkweed plants grown under the same experimental conditions, with AMF-specific primers (Krüger et al, 2009) demonstrated that the AMF mix consisted only of F. mosseae (details in Supplementary Material).…”
Section: Discussionmentioning
confidence: 99%